DEVELOPMENT OF TWO STAGE HYBRID FLOWSHOP MODEL CONSIDERING BATCH PROCESSOR & PARALLEL MACHINES - Nauli, Rahmawati
This study discusses the problem of scheduling two-stage hybrid flowshop with one batch processor machine in the first stage and parallel unrelated machines in the second stage. The problem in this study is that each job has a different release time and size which will then be grouped into batches. A batch processor machine can process several jobs simultaneously as long as the job size does not exceed the available machine capacity. After that each job will be processed in the second stage. In the second stage there is a unrelated parallel machine which means that each job has a different processing time for each machine. The scheduling model developed has criteria for minimizing makespan. The decision variables in this research are batch formation, determination of the number and sequence of batches to be processed and job assignments on parallel machines in the second stage. In addition to the mathematical model, heuristic algorithms are also proposed to solve problems in this scheduling model. Test results on analytical model solutions show that the computational time required will be higher when the number of jobs increases, the capacity of the batch processor is getting smaller, and the number of machines on stage 2 is increasing. While the results of heuristic algorithm solutions compared to the results of analytical model solutions show a gap of 2% - 27,8%.